ETHICAL HACKING - Galih Aryo Utomo (Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2019)
Ethical Hacking is done by companies in anticipation of system security loopholes. Ethical hacking is done by someone who has the ability like a hacker who is able to attack a system but has the motivation to help companies find security gaps that companies will use to evaluate their systems. This paper explains the importance of information and why it must be maintained and how an ethical hacker does his work.